Model Konseling Kelompok Berbasis Nilai Akidah Islam Terhadap Coping Stress - Anisatul Latifah; Anwar Sutoyo; Edy Purwanto (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2023)
Implementation of group counseling to increase the empathy of class VII students at SMP IT An Nahl. The type of research used is descriptive qualitative. The population in the study were all students of class VII at SMP IT An Nahl. The sampling method used simple random sampling technique as many as 8 students in class VII C. The results showed that the implementation of group counseling at the first meeting of students mostly did not respond to friends who were expressing opinions. There is only one student who is able to show empathy, such as respecting a friend who is talking by responding and giving feedback. This student is classified as an indicator of empathy. In the second meeting, there were six students who included indicators of empathy to think, understand, feel and communicate, such as students who actively asked questions, dared to express their opinions and were able to respond to their friends' responses. In the third meeting, all students actively argued and asked questions without being appointed by the group leader. This shows that empathy indicators have been realized by every student. Keywords: Coping stress; group counseling; islamic aqidah value Â